Diagnostics test criteria for COVID.19 and SARS-CoV-2 variants implications: brief literatura review - Vásquez-Velásquez , Cinthya (2022)
The rapid global spread of a new coronavirus initially named 2019-nCoV, detected in the city of Wuhan, China, now known as SARS-CoV-2, has posed new challenges for epidemiological surveillance. At the same time, the alarming growth of the pandemic makes it necessary to know and implement reliable diagnostic methods to detect and adequately treat patients. To this end, the most commonly used methods for diagnosis are: the immunochromatographic (IC) technique, which includes both antibody detection tests and antigen detection tests; and molecular diagnostic tests based on PCR technology, detecting virus quantitatively and qualitatively, such as qRT-PCR and LAMP, respectively. In the present review, we compare the diagnostic utility of LAMP, PCR and IC tests applied to the diagnosis of SARS-CoV-2, and how the different virus variants has impacted on its reliability. The necessary information was obtained from Scielo, Pubmed and Scopus databases.